The Phenomenon and Existence of Corruption in the 5.0 Era: Moral and Ethical Perspectives - Maulida Kelkusa; M Mahmudulhassan; Dito Anurogo; Ubed Abdilah Syarif (Walidem Institute and Publishing, 2023)
This study aims to 1) understand the meaning of corruption from a moral and ethical perspective, 2) find out the causes of people committing corruption, and 3) identify the impacts of corruption in the 5.0 era. Data collection methods using literature research techniques known as normative juridical approaches to literature evaluation are used. Following the moral and ethical basis derived from the Qur'an, Hadith, scientific papers, books, and articles, serve as a source of legal information. The findings of this study lead to the conclusion that corruption according to the moral and ethical perspective that has been discussed in the Qur'an Surah Al-Baqarah Verse 188 is taking the property of others in a vanity and deviant way of moral and ethical rules, and this act is a sin in the view of religions. Corruption has been regulated in the universal laws of all countries in the world, even the rules on combating corruption decide the harshest punishment is death, life imprisonment, or imprisonment according to the size of the property confiscated. Whereas in Islamic law perpetrators of corruption can be punished with chopping off hands or life imprisonment or ta'zir punishment (after the amount of property corrupted).